PENGARUH KOMPETENSI TERHADAP KINERJA PENGELOLA BADAN USAHA MILIK DESA (BUMDES) DI KABUPATEN KUANTAN SINGINGI PROVINSI RIAU - Dhea, Salwa; Raden, Ganarsih Lestari; Kurniawaty, Fitri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2023)
The research was carried out at village owned enterprises (BUMDes) which areincluded in the basic clasification in kuantan singingi regency.. the purpose ofconducting this research is.1) that influence the influence of knowledge that onperformance of BUMDes managers 2) that influence the skills that onperformance of BUMDes managers 3) to influence the influence of attitudes onthe performance of BUMDes managers on Kuantan Singingi Regency. The samplein this research were BUMDes managers which included a basic classification of165 BUMDes with a total of 255 managers.The independent variables in thisstudy are knowledge, skills and work attitudes, while the dependent variable is themanager's performance. The sample analysis method used is descriptive analysis,quantitative analysis is validity test, reliability test, hypothesis testing using WarpPLS program 0.7The results showed that 1) Knowledge variable (X1) has aneffect but not significant on performance (Y) because its significance value was0.06. This value is greater than the alpha value of 0.05.2) Skills (X2) and WorkAttitude (X3) variables have a significant on performance (Y) because thesignificance value is <0.01. the value are smaller than the alpha value of 0.05; 3)Of the two independent variables that have a significant effect, the Skills variable(X2) is the independent variables owned as the clear influence on performance(Y) because it has the largest path coefficient value, ie 0.22; Keywords: Knowledge, skills, work attitude and manager performance.